Sosialisasi Media Pembelajaran Berbasis Digital - Panjaitan, Dedy Juliandri; Ramadhani, Ramadhani; Sipahutar, Tuti Sumyati; Putri, Annisa Fadhillah (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service program (PKM) is one of the Tridharma activities of Tinngi College. In this case, the PKM activity was carried out at one of the elementary schools in Medan, namely Amir Hamzah Medan Private Elementary School. This PKM activity aims to help teachers socialize digital-based learning media that can be used in learning, especially for students at the elementary school level. This activity aims to enable teachers to apply digital-based learning media, so learning in class attracts more student interest. This PKM activity was carried out at SD Swasra Amir Hamzah Medan and was attended by 12 teachers offline (face to face). This activity is carried out in 3 stages. The first stage introduces digital learning media such as PowerPoint (PPT) and Canva. The second stage is to demonstrate the preparation of digital learning media, and in the final stage, the teacher can apply digital learning media in the classroom. The target outcomes that will be achieved in PKM activities are: (1) teachers can understand digital-based learning media, (2) increase teacher pedagogic competence, (3) teachers can develop digital-based learning media, (4) teachers can apply learning media in the classroom, (5) increase students' interest in learning. The implementation of PKM ran smoothly because all participants were active in the PKM activities and could apply them during the learning process in class